Pengaruh Ekspektasi Kinerja Mobile Banking dan Risiko yang Diterima Terhadap Niat Perilaku Nasabah Bank Syariah - Putri, Vingka Aulia; Aviva, Itsla Yunisva; Wehdawati, Wehdawati; Arifin, Muhammad Zainal (Forum Kerjasama Pendidikan Tinggi, 2025)
This study aims to analyze the influence of performance expectations and perceived risk on the behavioral intention to use mobile banking among customers of Bank Syariah Indonesia (BSI) in Palangka Raya City. The phenomenon of low mobile banking usage amid rapid digital transformation serves as the background for this research. A quantitative approach was used, employing a survey method through questionnaires distributed to 100 active BSI customers who use BSI Mobile services. Data analysis was conducted using multiple linear regression, t-test, F-test, and the coefficient of determination (R²). The partial test results show that performance expectations have a significant effect on behavioral intention (sig = 0.000 < 0.05), while perceived risk does not have a significant effect (sig = 0.670 > 0.05). However, simultaneously, both variables have a significant effect on customers’ behavioral intention (F = 48.485; p < 0.05). The adjusted R² value of 0.490 indicates that 49% of the variation in behavioral intention is explained by these two variables. The findings indicate that performance expectations positively influence the intention to use mobile banking, whereas perceived risk does not have a significant effect.